CREATIVE PERSONNEL MANAGEMENT AS AN OPERATIONAL TOOL FOR THE RESOURCE ADAPTATION OF AN ENTERPRISE TO THE DIGITIZATION OF BUSINESS PROCESSES - POMAZ, Oleksandr; HONCHARENKO, Alina; LOVUSHKO, Anastasiya; KURCHYTSʹKA, Inesa (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the role of creative personnel management as an operational tool for ensuring the resource adaptation of an enterprise to the conditions of digital transformation of business processes. The essence of creative management is revealed as a modern tool that ensures the development of labor potential, which is based on innovation, flexibility and involvement of personnel in the process of organizational change. The impact of digitalization on the structure and functioning of business processes is determined, the main challenges that arise in the field of human resource management in the context of technological dynamics are outlined. It is substantiated that creative personnel management is an effective operational mechanism for adapting personnel, information and organizational resources to new digital requirements. An approach to integrating creative management methods into the operational management system to increase labor productivity, innovative activity of employees and the sustainability of business processes is developed. The practical significance of the study lies in the possibility of using its results to form strategies for digital transformation of enterprises, develop personnel competencies, and improve the change management system. It is substantiated that digital transformation requires rethinking traditional approaches to human resource management and the formation of a new organizational culture based on innovation, flexibility and the development of digital competencies of employees. The content and mechanisms of creative personnel management as an operational tool for increasing the efficiency of human potential use in the digital economy are revealed. A model of resource adaptation of an enterprise is proposed, based on the integration of creative management practices, digital technologies and a system of continuous personnel development. It is concluded that creative personnel management contributes to increasing the competitiveness of an enterprise, optimizing business processes and forming strategic sustainability in the digital environment.